Sustainable Composites Using Landfill Bound Materials - Mort, Rebecca; Cecon, Victor S.; Mort, Paul; McInturff, Kelsey; Jiang, Shan; Vorst, Keith; Curtzwiler, Greg (Frontiers in Materials, 2022)
The demand for new methods of diverting materials from waste streams has grown as sustainability and landfill reduction goals continue to be set. Municipal solid waste combustion and waste-to-energy (WTE) facilities reduce landfill waste accumulation, but ash material by-products are commonly sent to landfills. In this work, we evaluate the potential for fly ash to be used as an inert filler in post-consumer recycled polyethylene to maximize landfill diversion of high-volume materials. Using fly ash from solid waste combustion as a filler increases landfill diversion, reduces associated costs, and offsets the cost of the recycling for post-consumer plastics by blending with a lost cost filler. Characterization of the fly ash revealed high variability in ash particle composition and size, which was expected due to the municipal solid waste source. A series of composites were compounded incorporating fly ash into recycled linear low-density polyethylene utilizing various compatibilizers. The composites were characterized for molecular interactions, thermal properties, mechanical properties and changes in melt processing via infrared spectroscopy, differential scanning calorimetry, electromechanical testing, and oscillatory melt rheology, respectively. Mechanical testing of the fly ash composites indicated that the fly ash did not significantly change the Young’s modulus or yield stress and the addition of various compatibilizer additives increased impact strength. The impact strength of the neat polymer decreased drastically from ~55 kJ/m2 to ~20 kJ/m2 at 5 wt. % fly ash. However, the addition of PGME compatibilizer at 0.75 wt. % increased the composite’s impact strength to roughly the same value as the neat polymer. Thus, the addition of a compatibilizer could be used to alter the fly ash filler composite’s resistance to flexural shock. These results indicate that fly ash can be added to recycled linear low-density polyethylene up to 10 % while maintaining physical properties.